Using Drama Activities in Taeaching Speaking Narrative Text for Senior High School (RETAIN, 2020)
Speaking is an essential skill that should be mastered by English learner. However, many students have difficulties in learning speaking skill. It is because many factors cause students difficulty learning, one of which is a lack of confidence. To overcome this problem, the teacher should create an effective method of teaching English, especially in speaking. Engaging in the curriculum 2013, students are required to be more active in teaching and learning process. That’s why the teacher should be more creative to teach speaking. One creative method that can be used by the teacher is Drama Activities. By using drama activities, students could learn how to speak English with an enjoyable environment. They can speak freely without worries because they can act in various ways and become what they want in the story. Students can be more active to speak and become attractive during the lesson.Thisresearch is aim to describe the implementation of Drama Activities in teaching speaking narrative text to the eleventh-grade students of SMAN Mojosari. The researcher also describes the students’ responses toward the technique. This research is descriptive qualitative research. The subject of this study is students of XI MIPA 4 SMAN Mojosari. The researcher using field notes and questionnaire sheet to gain the data.Theresult of this study shows that drama activities is easily implemented by the teacher. Most of the students respond to this technique with positive and agreed that drama activities bring a joyful environment to their class. Most of them said that drama activities could help them learning speaking in different ways and make them more confident to speak English. In the end, drama can make the students understand about the character from the story easily and could learn to express their feeling when speaking.Inconclusion, drama activities is a good technique that is suitable for teaching speaking narrative text. It makes the learning activities become student-centred and it helps the students confident to speak because they learn in fun and joy.